Analisis Prosedur Pengajuan Klim Tabungan Hari Tua (THT) Pada PT. Taspen (Persero) Kantor Cabang Medan - Syahfitri, Mulia; Muhammad Arif (Lembaga Pengembangan Kinerja Dosen, 2024)
PT. Taspen is an Indonesian state-owned institution which operates in the insurance sector, Old Age Savings (THT), and pension funds for civils servants and state officials. Thus, this company has a task, one of which is to provide services in terms of the Old Age Savings (THT) program. There are various procedures that must be provided in providing these services so that participants who administer the program are more coordinated and directed. The reason for carrying out this research is to obtain the goal to be achieved, namely to find out the procedure to submitting a Old Age Savings (THT) claim at PT. Taspen is carried out. This study used descriptive qualitative method. The result of this research is that you must complete the required documents first in order to be able to submit a claim for Old Age Savings (THT).